A randomized phase 2 trial of pembrolizumab versus pembrolizumab and acalabrutinib in patients with platinum‐resistant metastatic urothelial cancer. Issue 20 (5th August 2020) - Zhang, Tian; Harrison, Michael R.; O'Donnell, Peter H.; Alva, Ajjai S.; Hahn, Noah M.; Appleman, Leonard J.; Cetnar, Jeremy; Burke, John M.; Fleming, Mark T.; Milowsky, Matthew I.; Mortazavi, Amir; Shore, Neal; et al.
Abstract : Background: Inhibition of the programmed cell death protein 1 (PD‐1) pathway has demonstrated clinical benefit in metastatic urothelial cancer (mUC); however, response rates of 15% to 26% highlight the need for more effective therapies. Bruton tyrosine kinase (BTK) inhibition may suppress myeloid‐derived suppressor cells (MDSCs) and improve T‐cell activation. Methods: The Randomized Phase 2 Trial of Acalabrutinib and Pembrolizumab Immunotherapy Dual Checkpoint Inhibition in Platinum‐Resistant Metastatic Urothelial Carcinoma (RAPID CHECK; also known as ACE‐ST‐005) was a randomized phase 2 trial evaluating the PD‐1 inhibitor pembrolizumab with or without the BTK inhibitor acalabrutinib for patients with platinum‐refractory mUC. The primary objectives were safety and objective response rates (ORRs) according to the Response Evaluation Criteria in Solid Tumors, version 1.1. Secondary endpoints included progression‐free survival (PFS) and overall survival (OS). Immune profiling was performed to analyze circulating monocytic MDSCs and T cells. Results: Seventy‐five patients were treated with pembrolizumab (n = 35) or pembrolizumab plus acalabrutinib (n = 40). The ORR was 26% with pembrolizumab (9% with a complete response [CR]) and 20% with pembrolizumab plus acalabrutinib (10% with a CR). The grade 3/4 adverse events (AEs) that occurred in ≥15% of the patients were anemia (20%) with pembrolizumab and fatigue (23%), increased alanine aminotransferase (23%), urinary tract infections (18%), and anemia (18%) with pembrolizumab plus acalabrutinib. One patient treated with pembrolizumab plus acalabrutinib had high MDSCs at the baseline, which significantly decreased at week 7. Overall, MDSCs were not correlated with a clinical response, but some subsets of CD8+ T cells did increase during the combination treatment. Conclusions: Both treatments were generally well tolerated, although serious AE rates were higher with the combination. Acalabrutinib plus pembrolizumab did not improve the ORR, PFS, or OS in comparison with pembrolizumab alone in mUC. Baseline and on‐treatment peripheral monocytic MDSCs were not different in the treatment cohorts. Proliferating CD8+ T‐cell subsets increased during treatment, particularly in the combination cohort. Ongoing studies are correlating these peripheral immunome findings with tissue‐based immune cell infiltration. Abstract : In this randomized phase 2 study of metastatic urothelial cancer, a combination of pembrolizumab and a Bruton tyrosine kinase inhibitor (acalabrutinib) does not improve clinical outcomes in comparison with pembrolizumab alone. Comprehensive flow cytometry is used to evaluate circulating immune cells during treatment.